Analyzing the balance between Patents Laws of India and Public Health Issues: A Socio-legal Study - Dr. Samrat Datta (Drugs and Cell Therapies in Hematology, 2021)
The spread of various infectious diseases around the world and the lack of medicines and healthcare facilities necessitated striking a balance between patent protection laws and the right to public health. This article talks about the evolution of patent laws around the world with a special reference to their relevance in India from the pre-independence time to the post-independence era with greater emphasis on the provisions enumerated in the Patent Act relating to Public Health. The aim of this article is to establish a relationship between public health and patent laws while simultaneously trying to establish their growing importance by the day in the wake of deadly diseases and expensive cures. Furthermore, the article discusses various kinds of pharmaceutical patents recognized in India by the Indian Patent Office while seeking to analyze the concept of patent licensing in this regard and how the transferability of pharmaceutical patents benefits a common man without any hindrance to the rights of the innovators.